PENGETAHUAN REMAJA PUTRI TENTANG KANKER PAYUDARA - Usianti, Arilia; Fauzan, Suhaimi; Rahmawati, Nadia; S.U. Adiningsih, Berthy; Fahdi, Faisal Kholid (Sekolah Tinggi Ilmu Keperawatan Muhammadiyah Pontianak, 2024)
The most common cancer case in Indonesia is breast cancer, with 58,256 cases or 16.7% of the total 348,809 cancer cases. Lack of education about breast cancer since adolescence to prevent breast cancer is one of the factors causing the high incidence of breast cancer. This study aimed to determine the knowledge of teenage girls about breast cancer at SMP Negeri 02 Mandor. This research employs a descriptive-quantitative design. The sample is determined using the stratified random sampling method followed by a simple random sampling method with a total of 116 respondents. Data collection was conducted by a questionnaire divided into respondent characteristics and knowledge about breast cancer. The data analysis technique involves frequency distribution and percentage. The univariate analysis results indicated that the majority of respondents were 13 years old, numbering 52 individuals (44,8%), there were 59 individuals (50,9%) in grade 8,63 individuals (54,3%) had never received information about breast cancer, and 116 individuals (100%) had no family history of breast cancer. There were 65 individuals (56,0%) with a poor knowledge category.